2019
DOI: 10.1002/alr.22406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endoscopic sinus surgery on objective and subjective measures of cognitive dysfunction in chronic rhinosinusitis

Abstract: BackgroundChronic rhinosinusitis (CRS) is a common condition that has been associated with cognitive dysfunction. The purpose of this study was to evaluate the effect of endoscopic sinus surgery (ESS) on the subjective and objective measures of cognitive dysfunction and related quality‐of‐life measures in CRS.MethodsThirty‐five adults with CRS refractory to medical therapy were prospectively enrolled. Preoperatively and postoperatively (≥4 months), subjects completed objective neurocognitive evaluation with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Several studies have shown a correlation between the presence of pro-inflammatory molecules and cognitive dysfunction [3][4][5]. Existing hypotheses postulate an individual effect of particular inflammatory mediators on cognitive function in CRS with or without nasal polyposis [2]. Referring to this study [2], the inflammatory cascade might impact cognition.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Several studies have shown a correlation between the presence of pro-inflammatory molecules and cognitive dysfunction [3][4][5]. Existing hypotheses postulate an individual effect of particular inflammatory mediators on cognitive function in CRS with or without nasal polyposis [2]. Referring to this study [2], the inflammatory cascade might impact cognition.…”
Section: Introductionmentioning
confidence: 68%
“…Existing hypotheses postulate an individual effect of particular inflammatory mediators on cognitive function in CRS with or without nasal polyposis [2]. Referring to this study [2], the inflammatory cascade might impact cognition.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations